Pemanfaatan Leaflet Untuk Meningkatkan Pengetahuan Dan Perilaku Hygiene Sanitasi Penjamah Makanan Pada Warung Makan Di Pasar Beringkit Kabupaten Badung: Effectiveness of Leaflet-Based Education in Improving Food Handlers' Knowledge and Hygiene-Sanitation Practices at Food Stalls in Beringkit Market, Badung Regency - Ni Kadek Yulia Dwi Yunitha; I Nyoman Sujaya; I Ketut Aryana; I Made Bulda Mahayana (Poltekkes Kemenkes Denpasar, 2026)
Title: Effectiveness of Leaflet-Based Education in Improving Food Handlers' Knowledge and Hygiene-Sanitation Practices at Food Stalls in Beringkit Market, Badung Regency Background : Food is an essential human need that must be maintained in quality to avoid contamination that can cause disease. Food handlers in food stalls are key parties in implementing food hygiene and sanitation. This study aims to determine the use of leaflets to improve knowledge and hygiene sanitation behavior of food handlers at food stalls in Beringkit Market, Badung Regency Method : The method used is Pre-Experimental with One Group Pretest -Posttest design involving a total population of 35 food handlers Result : Before the counseling, the average value of food handlers' knowledge was 43.00 and after the counseling, there was an increase in the average value to 55.86. While the behavior of respondents before the average value of food handlers was 45.43 and after the counseling, there was an increase in the average value to 60.57. Conclusions : The results of the analysis showed a significant difference between before and after the counseling, both in knowledge and behavior with p value = 0.000 (<0.05). It is hoped that food handlers with negative habits are advised to pay more attention to the use of personal protective equipment such as masks and gloves even though they feel uncomfortable, because this is very important in preventing cross-contamination